المكان في قصيدة: زنزانة العذاب 73 لمفدي زكرياء بين التشكل والجمالية (مجلة الواحات للبحوث والدراسات, 2023)
ملخص:تشي قصيدة زنزانة العذاب 73 انطلاقا من عنوانها على قسوة التجربة للشاعر الجزائري مفدي زكرياء من خلال مكوثه في سجن بربروس (سركاجي) سنة 1957م، وهي تجربة جعلته يعبر عن معاناته داخل زنزانة صغيرة وضيقة مُورِس عليه فيها أبشع أنواع العذاب، فأنشد هذه القصيدة واصفا فيها هذا المكان الذي أحدث في نفسه تماهيا بسبب الوحدة والعزلة فانزاح من دلالة الاحتواء إلى دلالات أخرى، وانطلاقا من هذا الطرح تهدف هذه الدراسة الموسومة بـــ: المكان في قصيدة زنزانة العذاب 73 بين التشكل والجمالية" إلى الكشف عن الطريقة التي رسم بها الشاعر هذا المكان من ناحية البنائية والفنية، فكيف كان تشكل هذا المكان؟ وماهي أهم الآليات التي اعتمدها الشاعر في تشكله؟ وما هي الأساليب الفنية التي وظفها لإبراز مظاهر وتشكل هذا المكان، وفيم تجلت هذه الفنيات؟ وقد اعتمدنا في هذه الدراسة على المنهج البنيوي للكشف عن طريقة انبناء هذا المكون الخطابي، وكذا بعض آليات المنهج الفني لإبراز أهم القيم الجمالية في القصيدة. كما أن الدراسة قد توصلت إلى نتائج أهمها نجاح الشاعر في إضفاء صفة الأنسنة على السجن، وجعل المكان منغلقا هندسيا منفتحا شعوريا.كلمات دالة: مكان، تشكل، جمالية، فنية، مفدي زكرياء. Abstract: The poem Cell of Torment 73 based on its title betokenss the bitterness of the experience of the Algerian poet Mufdi Zakaria during his oubliette in Barbaros jail (Sarkaji) in the year 1957 AD, an experience that made him vent his oppression inside a narrow and incommodious cell in which he was subjected to the ugliest  kinds of torment, so he set forth this poem describing in  that sordid place. The place that haunted him because of loneliness and isolation, so it shifted from the denotation of containment to other connotations.Based on this proposition, this study, entitled “The place in the poem Cell of Torment 73, between morphology and aesthetics,” tries to divulge the way the poet pictured this place in terms of structuralism and art. How was this place shaped? What are the most important mechanisms that the poet relied on in its description? What are the artistic technioques that he used to accentuate the shape and formation of that place, and in how were these techniques manifested?In our study, we relied on the structural approach to reveal the method of constructing this rhetorical component, as well as some mechanisms of the artistic approach to accentuate the most important aesthetic values in the poem. Key words: place, formation, aesthetic, artistic, Mufdi Zakaria